2015
DOI: 10.1016/j.healun.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and left ventricular assist device implantation

Abstract: This study assessed the use of the MoCA in patients with end-stage HF being evaluated for advanced surgical therapy. We found the MoCA to be a rapid, simple, and powerful tool for detecting cognitive impairment in these patients. MCI was highly prevalent in the cohort. Significant improvement in overall MoCA score was noted after LVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…Limited data are available on the effects of long‐term support with LVAD on cognitive function. A recent study in patients with end‐stage HF demonstrated that haemodynamics and cognitive function improved significantly at 8 months after LVAD implantation, suggesting that improvement in cardiac output and cerebral perfusion may have a beneficial impact on cognitive function . Studies have shown that improvement of cognitive function with LVAD is independent of the mode of flow support (pulsatile vs. continuous) .…”
Section: Interactions Related To Heart Failure Treatmentmentioning
confidence: 99%
“…Limited data are available on the effects of long‐term support with LVAD on cognitive function. A recent study in patients with end‐stage HF demonstrated that haemodynamics and cognitive function improved significantly at 8 months after LVAD implantation, suggesting that improvement in cardiac output and cerebral perfusion may have a beneficial impact on cognitive function . Studies have shown that improvement of cognitive function with LVAD is independent of the mode of flow support (pulsatile vs. continuous) .…”
Section: Interactions Related To Heart Failure Treatmentmentioning
confidence: 99%
“…The cumulative incidence of cognitive impairment in the first year after LVAD implantation was 29.2% . However, most studies found that cognition improved in the first 1 to 2 years after LVAD implantation . Risk factors for cognitive decline in this population include older age, higher CHADS2 risk score, statin use, history of stroke and hypertension, and destination therapy (as opposed to a bridge to transplantation) .…”
Section: Discussionmentioning
confidence: 94%
“…Although long‐term cognitive deficits are rare after cardiovascular procedures , encephalopathy and delirium can occur postoperatively, any time during acute care hospitalization, and sometimes during inpatient or subacute rehabilitation . The incidence of cognitive impairment in patients with advanced heart failure before LVAD implantation was 67% in 1 study . The cumulative incidence of cognitive impairment in the first year after LVAD implantation was 29.2% .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that cognitive impairment is common up to 1-year post LVAD implant, and that such impairment is profound in older adults, aged 70 years and older (32,33). Cognitive dysfunction is common in heart failure, and its negative effect on the patient's QOL is widely known.…”
Section: Discussionmentioning
confidence: 99%